ARE MORAL PHILOSOPHERS MORAL EXPERTS? - Gesang, Bernward (Bioethics, 2010)
In this paper I examine the question of whether ethicists are moral experts. I call people moral experts if their moral judgments are correct with high probability and for the right reasons. I defend three theses, while developing a version of the coherence theory of moral justification based on the differences between moral and nonmoral experience: The answer to the question of whether there are moral experts depends on the answer to the question of how to justify moral judgments. Deductivism and the coherence theory both provide some support for the opinion that moral experts exist in some way. I maintain – within the framework of a certain kind of coherence theory – that moral philosophers are ‘semi-experts’.